Rank correlation methods. - Kendall, Maurice G. (London: Charles Griffin & Company Ltd, 1962)
This volume examines rank correlation a rather neglected branch of the theory of statistical relationship. It includes topics like: measurement of rank correlation; tied ranks; test of significance; problem of m ranking; ranks and variate values; paired comparison and others.
Includes index
II 17/01/2019
Loans
Keywords: Correlation (Statistics)